PENERAPAN MODEL PEMBELAJARAN GUIDED INQUIRY BERBANTUAN PRAKTIKUM TERHADAP KETERAMPILAN PROSES SAINS SISWA PADA MATERI GELOMBANG BUNYI - Paridah, Ipi; Saefullah, Asep; Antarnusa, Ganesha (JURNAL PEMBELAJARAN FISIKA, 2024)
This research aims to determine the effect of students' science process skills using the guided inquiry learning model assisted by practicum on sound wave material at SMA Negeri 6 Serang City. The research method used is quasi-experimental with a one group pretest-posttest design approach. The research results show that the average N-gain value is 0.11 in the low category for the pretest and the posttest N-gain is 0.49 in the medium category. The average percentage result on the students' science process skills observation sheet is 78.40% in the good category. Based on the research results, there is an influence of the application of the guided inquiry learning model assisted by practicum on students' science process skills in the material of sound waves.